EVALUATION OF ENERGY COGENERATION FROM SUGAR CANE BAGASSE - Abreu Elizundia, Hanserth; González Cortés, Meilyn; Rico Ramírez, Odlanier; Morales Zamora, Marlén; Espinosa Pedraja, Rubén (Centro Azúcar Journal, 2016)
In this paper were simulated and evaluated five alternatives of cogeneration scheme that promote a higher production of thermal and electrical energies as well as its right management. The first three alternatives are directed to increasing the boiler pressure and a change of steam turbines which are the extraction-condensation type, and then the fourth alternative proposed a boiler change to implement a bubbling fluidized bed and finally in the fifth alternative a scheme of biomass gasification is analyzed. All scheme were analyzed energetic and exergetically. The five cogeneration alternatives were simulated in ASPEN PLUS; they showed that the largest surplus bagasse and electricity are obtained with the scheme of a biomass gasification and the worst results in these parameters were obtained in the alternative that function in low pressure and temperature parameters .